Comportamento informacional em tempos de autoinfoeducação - Maria Leonor Amorim Antunes (2022)
Information society and knowledge society are common epithets for contemporary society. Judging that the liquid times of our current society bring the subject closer to information, without this approach necessarily translating into a knowledge society, this thesis is concerned with the informational behavior of a youth in a situation of social vulnerability. More precisely, about how the wide offer of digital information can contribute to Brazilian education – especially to its public school and its library. Therefore, the present research aimed to ponder substrates to promote the informational cycle, the appreciation of knowledge and the search for information; which is all covered in a proposal here called selfinfoeducation. Out of an appreciative and interpretative character, the research developed has a qualitative nature and resorts to a documentary and bibliographic research, as a methodology, to enable the construction of a contextual narrative, on the three aforementioned pillars in which selfinfoeducation is conceived: the logic of networks , the logic of the adolescents, and the action of mentalities. This thesis understand that the greatest challenge of contemporary basic education lies in the distance between this youth and the school in the lack of meaning that young people attribute to it; partly because of its analogical character, partly because they do not see in school, a correspondence to their reality in the world. Therefore, the solution thought was the proposition of an information literacy curriculum, to be worked on at school, by the librarian. The research findings indicate that investing in raising awareness on the search for information (working on mentalities) is really necessary, since sensitivity, mediated by dialogue, has an awarenessraising power about the existence of information that, when properly worked on, has a transforming potential of reality.